Implementation of Deep Breath Relaxation Techniques As An Effort to Overcome Shortness Of Breath in Congestive Heart Failure Patients - Asep Gunawan; Nur Hidayat; Sinta Siti Rahmah (Jurnal Vocational Nursing Sciences (VNUS), 2023)
Introduction: Congestive heart failure (CHF) is a cardiovascular disease that is defined as a deadly disease in the world. CHF is a condition in which the heart is unable to pump blood to meet the needs of oxygen and nutrients in the body's tissues. Objective: To present care with deep breathing relaxation interventions as an effort to overcome shortness of breath in congestive heart failure patients with ineffective breathing patterns. Method: The research design used is descriptive analysis with a case study approach. Subjects in this case study were adult patients with congestive heart failure (CHF) and ineffective breathing patterns. Data collection techniques include interviews, observation, physical examination, and documentation studies. Result: The case study at the assessment stage found that the client complained of shortness of breath. The intervention and implementation used to reduce shortness of breath is by providing breathing relaxation exercises for 10 minutes when complaints of shortness of breath are felt. After the intervention, the client's breathing frequency decreased from 28 x/minute to 22 x/minute, while the subjective data from the anamnesis showed that the client's shortness of breath was reduced. Conclusion: Nursing care for patients with congestive heart failure (CHF) and shortness of breath is well managed. Providing deep breathing relaxation interventions is effective in reducing respiratory frequency.